A revision of the South American species of the ant-mimicking spider genus Myrmecotypus O. Pickard-Cambridge, 1894 (Araneae: Corinnidae: Castianeirinae) - Silva-Junior, Cláudio J.; Bonaldo, Alexandre B. (Zootaxa, 2024)
The ant-mimic spider genus Myrmecotypus O. Pickard-Cambridge, 1894 is revised for the first time from South America, increasing the number of species known from that region from seven to 15, totaling 23 known species in the genus. The identity of three Neotropical species currently in Apochinomma Pavesi, 1880 was recovered and they are transferred to Myrmecotypus: M. formica (Simon, 1896) comb. nov., M. formicoides Mello-Leitão, 1939 comb. nov., and M. dacetonoides (Mello-Leitão, 1948) comb. nov.. Myrmecotypus formicoides is proposed as a junior synonym of M. niger Chickering, 1937 and M. dacetonoides is considered the senior synonym of M. iguazu Rubio & Arbino, 2009. Apochinomma myrmecioides Mello-Leitão, 1922 and A. bilineatum Mello-Leitão, 1939 are also transferred to Myrmecotypus but considered as a nomina dubia. Myrmecotypus rubioi Pett & Perger, 2021 is transferred to Grismadox Pett, Perger & Rubio, 2022. Myrmecotypus tahyinandu Perger & Rubio, 2020 and M. haddadi Perger & Rubio, 2021 are recorded from Brazil for the first time, and M. rubrofemoratus Perger & Rubio, 2021 is recorded from Peru for the first time. Eight new species are proposed: M. drogon spec. nov. (♂), M. regianeae spec. nov. (♂ ♀), M. candianii spec. nov. (♂ ♀), M. balerion spec. nov. (♂ ♀), M. ciriaco spec. nov. (♂ ♀), and M. rapaxoides spec. nov. (♂ ♀) from Brazil, M. ednae spec. nov. (♂ ♀) from Brazil and Peru, and M. atratoides spec. nov. (♀) for Brazil, Ecuador, and Colombia. All South American species are rediagnosed and mapped, and a key to all Myrmecotypus species is provided.